An Analysis on Students’ Speaking Anxiety at Tenth Graders of MA Mu’allimat NW Pancor - Dwimaulani, Astrid (VELES Voices of English Language Education Society, 2018)
This study is aimed at investigating students’ speaking anxiety at the tenth graders of Religion class of MA Mu’allimat NW Pancor in the academic year 2017-2018. The purposes of the study were: 1) to know what kinds of anxiety the students experience in speaking English; 2) to find the factors of students’ speaking anxiety; 3) to learn on what proper method and technique to decrease students’ speaking anxiety. This research was a descriptive qualitative research. The participants were consisted of 15 students and have been chosen using purposive sampling. Finding reveals that there are three types of students’ anxiety, which are trait anxiety, state anxiety and specific-situation anxiety. For the result of questionnaire, the formula that used was the gained score of respondent divided to total score of five aspects times 100%. The result showed that there were 73.3% agree respond which indicated students faced English speaking anxiety, 17.62% chose neutral, and the rest chose disagree option with 9.05% percentage. Beside questionnaire, the observation and interview result also showed that majority of the students had English speaking anxiety with various factors.